2006
DOI: 10.1128/jvi.80.6.2609-2620.2006
|View full text |Cite
|
Sign up to set email alerts
|

The α-TIF (VP16) Homologue (ETIF) of Equine Herpesvirus 1 Is Essential for Secondary Envelopment and Virus Egress

Abstract: The equine herpesvirus 1 (EHV-1) ␣-trans-inducing factor homologue (ETIF; VP16-E) is a 60-kDa virion component encoded by gene 12 (ORF12) that transactivates the immediate-early gene promoter. Here we report on the function of EHV-1 ETIF in the context of viral infection. An ETIF-null mutant from EHV-1 strain RacL11 (vL11⌬ETIF) was constructed and analyzed. After transfection of vL11⌬ETIF DNA into RK13 cells, no infectious virus could be reconstituted, and only single infected cells or small foci containing up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 69 publications
0
35
0
Order By: Relevance
“…For example tegument protein pUL48 (VP16) interacts with glycoprotein H as well as inner tegument protein pUL36 and capsid-associated proteins pUL35 and pUL38 (24,38), thereby helping to bridge the (12,27,41). Although it is not known whether these interactions would occur in the absence of an intermediate virion, the interaction between the envelope glycoproteins and the capsid is central to driving viral egress.…”
Section: Discussionmentioning
confidence: 99%
“…For example tegument protein pUL48 (VP16) interacts with glycoprotein H as well as inner tegument protein pUL36 and capsid-associated proteins pUL35 and pUL38 (24,38), thereby helping to bridge the (12,27,41). Although it is not known whether these interactions would occur in the absence of an intermediate virion, the interaction between the envelope glycoproteins and the capsid is central to driving viral egress.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mechanism of ORF52's function(s) requires a better understanding of the protein's interactions with other viral proteins and cellular machinery involved in the formation and release of virions from the infected cell. Studies have identified alphaherpesvirus tegument proteins that are specifically required for virion morphogenesis in the cytoplasm, such as pseudorabies virus UL37 (25) and UL48 in both pseudorabies virus and HSV-1 (16,49). Undoubtedly, other tegument proteins are also involved in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both glycoprotein E (gE) and gI, which form a noncovalently linked complex in infected cells and virions, are essential for the growth of both viruses, at least in certain cell types, while they are dispensable in all other alphaherpesviruses tested (3,8,25,37,42,50,63,65). In contrast, the major viral transactivator encoded by VZV ORF10 (MDV UL48) is dispensable for the growth of either virus, but is essential for most related viruses (17,19,20,58,61). In this context, it must be noted that the MDV UL49 product, the ORF9 homologue of VZV, was shown to be absolutely required for the growth of the chicken virus.…”
Section: Varicella-zoster Virus (Vzv)mentioning
confidence: 99%